2017
DOI: 10.1007/s10877-017-0039-6
|View full text |Cite
|
Sign up to set email alerts
|

Suprasternal notch echocardiography: a potential alternative for the measurement of respiratory variation in aortic blood flow peak velocity in mechanically ventilated children

Abstract: We conducted a prospective, observational study to investigate the relationship between the respiratory variation in aortic blood flow peak velocity (ΔVPeak) measured by echocardiography in the proximal ascending aorta from the suprasternal notch window and the ΔVPeak measured at the level of the aortic annulus from the classical apical five-chamber view. We studied children aged from 1 to 10 years referred for surgery under general anesthesia with positive pressure ventilation, after induction of general anes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This method is useful when access to the chest wall is limited during surgery. A significant relationship between the ΔVpeak recorded via the suprasternal notch view and that recorded via the apical 5-chamber view (r = 0.62, P = 0.003) has been previously reported [34].…”
Section: Potential Predictors Of Fluid Responsivenesmentioning
confidence: 64%
“…This method is useful when access to the chest wall is limited during surgery. A significant relationship between the ΔVpeak recorded via the suprasternal notch view and that recorded via the apical 5-chamber view (r = 0.62, P = 0.003) has been previously reported [34].…”
Section: Potential Predictors Of Fluid Responsivenesmentioning
confidence: 64%
“…Previous studies have identified the relationship between fluid responsiveness and respiratory variation in the arterial blood flow peak velocity in the ascending aorta and/ or the proximal branches of the aorta. 7,8,22 We also observed the respiratory variation of the internal carotid artery blood flow peak velocity when we checked the blood flow to the brain using transfontanelle Doppler ultrasound. The purpose of this study was to evaluate the potential role of point-of-care transfontanelle ultrasonography by determining whether the respiratory variation of the internal carotid artery blood flow peak velocity measured by transfontanelle Doppler ultrasound can predict fluid responsiveness in pediatric cardiac patients.…”
Section: What We Already Know About This Topicmentioning
confidence: 99%
“…ΔVpeak can also be measured via the suprasternal notch view, which has more practicality during surgery compared to the apical 5-chamber view 41,42 . Other variants of this technique have been deduced.…”
Section: Fluid Responsivenessmentioning
confidence: 99%